Archaeologists-in-Training: Students of the British School of Archaeology in Jerusalem, 1920-1936. (2nd February 2012) - Thornton, Amara
Compiled in the process of doctoral research, this list of students at the British School of Archaeology in Jerusalem covers the terms of the School's first two directors, John Garstang and John Crowfoot. It has been gathered from the School's Minute Books, now in the archive of the Palestine Exploration Fund, and from contemporary published reports in the Palestine Exploration Quarterly. By naming and enumerating the students at this institution, still in existence today, the diaspora of and networks inherent in archaeological training during the early years of professionalization become clear. The data also includes the background and education (where known) of these prospective archaeologists, an important factor in evaluating issues of gender, class and education in the history of the discipline.